Coconut shell ash as cementitious material in concrete: a review - Bheel, Naraindas; Mangi, Sajjad Ali; Meghwar, Shanker Lal (Penerbit Universiti Kebangsaan Malaysia, 2021)
In recent years, there has been great concern about introducing new supplementary cementitious materials (SCM) in place of ordinary Portland cement (OPC) in concrete. The aim of this study is to check the behavior of coconut shell ash (CSA) with various proportions in concrete. Coconut shell is available in abundant quantity in local agricultural fields and considered as waste product. On the other hand, cement production emits a lot of toxic gases in the atmosphere which causes environmental pollution and greenhouse gases. Thus, CSA might be utilized as a cementitious material in concrete for sustainable development. This review article provides a detailed overview of the fresh and mechanical properties of various research studies. It is found that by incorporating the 10% of CSA into concrete results in the improvement of mechanical properties of concrete such as compressive, split tensile strength and flexural strength of concrete after every curing day respectively. Moreover, the modulus of elasticity enhanced while using 10% of CSA in concrete and the workability of fresh concrete was declined as the percentage of CSA increases. In addition to that, the use of CSA in concrete can reduce the total carbon foot print while reducing the overall cost of concrete manufacturing.